School type as a determinant of students' performance in WASSCE in Lagos state (2007)
This study considered the impact of school type (Public - Private) on the performance of students in the West African Senior School Certificate Examination in Lagos State in English, Mathematics and Biology. The May/June result of thirty schools (15 Public and 15 Private) covering the six educational districts of Lagos State were used for tire study. The result of the students for three years (2004, 2005 and 2006) urns obtained from the West African Examinations Council (WAEC) and analyzed using the independent T-Test stastics. The outcomes of the analysis revealed that the private schools performed better than the public schools generally, while the Unity Schools performed better than the Missionary Schools in the West African Senior School Certificate Examination in Lagos State within the three years investigated. It was also discovered that the public schools had large candidates to manage during the examinations - and this would have accounted, partially, for their poor performances, amongst other discoveries. Valid recommendations were made based on the findings of the study.